Noise Analysis of wet Multi-disc Brake Used Complex Eigenvalue - Tian-hong Luo; Ting-qiong Cui; De-shan Li; Wen-jun Luo; Chao Lin (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper proposed an analysis model and a complex-eigenvalue-based algorithm of wet multiple disc brake (WMDB) noise. Firstly, the damping and stiffness between the brake disc and the friction plate were introduced based on the consideration of the slight rotation of the braking system and damping characteristics of brake oil. Then, the friction coupling mathematical model and the finite element model (FEM) of the braking system were established. The occurrence tendency of brake squeal was judged according to the real part (positive or negative value) of characteristic roots of the complex eigenvalue. The relative error between the numerical analysis results and the finite element analysis results was 4%, indicating that braking speed and braking pressure had little effect on brake noise. During the braking system design, under the premise that the braking performance is not affected, the friction material with the lower stiffness should be used as possible. Moreover, properly decreasing the friction coefficient between the friction linings and dual steel disc will reduce the brake noise. Therefore, the proper combination of the parameters was deduced to obtain the stable frequency response of the braking system.